Antimalaria Effect of the Ethanolic Stem Bark Extracts of Ficus platyphylla Del - Isma'il Shittu; Amlabu Emmanuel; Andrew Jonathan Nok (Journal of Parasitology Research)
The antimalarial effect of the ethanolic stem bark extract of Ficus platyphylla Del was evaluated against Plasmodium berghei infection in mice. Nontreated, experimental control mice died of fulminant parasitemia from day 7 to 9 post-infection but mice treated with the extract at 300 mg/kg showed markedly reduced parasitaemia bouts of 43.50% and a mean survival time of 28 days postinfection. The plant extract prevented a drastic reduction in PCV showing its efficacy in ameliorating anaemic conditions in Plasmodium berghei-infected mice. Histological examination of liver tissues of treated and untreated mice further supports the antimalaria potential of this plant. This observation validates the traditional use of this plant for the treatment of malaria.